Notes on Early Land Plants Today. 22. New combinations and new synonymy in Omphalanthus and Aureolejeunea (Lejeuneaceae, Marchantiophyta) - Gradstein, S. Robbert (Phytotaxa, 2013)
Omphalanthus Gottsche et al. (1845a: 303) and Aureolejeunea Schuster (1978: 428) (Lejeuneaceae Cavers (1910: 291) tribe Lejeuneeae Dumortier (1822: 111)) are two small, closely related Afro-American genera of eight and six currently accepted species, respectively. Omphalanthus is the most widespread of the two and occurs commonly throughout tropical America. The distribution of Aureolejeunea is more restricted and it is mainly confined to high elevations in the Andes. In Africa the two genera are very rare and represented by only one species each.